قراءة في أحكام الافراج المشروط في التشريع الجزائري - طواهري, اسماعيل (جامعة الوادي.University eloued, 2022)
لإفراج المشروط هو أحد أهم أسالب المعاملة العقابية الحديثة، مجسدا للتفريد العقابي أو ما يعرف بتفريد برامج إعادة تأهيل المحبوس، التي أعطت نتائج ايجابية لإعادة دمج المحبوسين في المجتمع وتهذيبهم بتقويم سلوكهم ومطابقته للقانون، إذ لم تبق بهم خطورة إجرامية تجعل وجودهم داخل المؤسسة العقابية في صالحهم ولا في صالح المجتمع، مما يبرر إطلاق سراحهم ضمن ما تتطلبه المقتضيات الضرورية Parole or conditionalrelease is one of the most significant forms of modern punitive treatment, reflecting the punishment or what is known as rehabilitation programmes for prisoners. They have given positive results to the reintegration of prisoners into society and to the rectification of their behaviour and conformity with the law. They were not left with a criminal danger that makes their presence inside the penitentiary institution in their favour. Nor is it in the interest of society, which justifies their release within what is required by the necessary requirements
Keywords: لإفراج؛ المشروط؛ المحبوس؛ العقاب؛ جريمة; for release; conditional; imprisoned; punishment; Crime